Pemanfaatan Al-Qur’an Digital di Pondok Pesantren Al-Asy‘ariyyah: Antara Praktikalitas Teknologi dan Pelestarian Mushaf - Arum Luqmana Sari; Arif Al Wasim (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
This study examines the use of digital Qur’an applications at Pondok Pesantren Al-Asy‘ariyyah Kalibeber by focusing on the relationship between technological practicality and the preservation of the printed mushaf. Employing a qualitative method with a descriptive-analytical approach, data were collected through observation, in-depth interviews, and documentation involving pesantren leaders, teachers, active students, and senior students. The findings reveal that the digital Qur’an is accepted as a supporting learning medium due to its practicality and efficiency, particularly for students with sufficient digital literacy. However, the printed mushaf remains the primary reference in Qur’anic learning as a form of respect for its sacred value, the pesantren’s scholarly tradition, and the limited digital literacy among senior students and teachers. This study demonstrates that the utilization of the digital Qur’an in the pesantren context is selective and contextual, serving as a complementary tool rather than a replacement for the mushaf. These findings indicate that pesantren are capable of responding to technological developments in a balanced and tradition-oriented manner.